The convergence of Nahdlatul Ulama and Jamaah Tabligh traditions in Temboro Village, Magetan, East Java - Nurhayati, Anifa; Imam Muhsin; Prabowo, Thoriq Tri (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
Temboro Village in East Java, known as the "Medina Village" due to its Araban atmosphere, underwent a cultural transformation when the al-Fatah Temboro Islamic Boarding School shifted its preaching orientation from salafiyah-NU to salafiyah-Jamaah Tabligh in 1989. This transformation did not erase NU traditions but rather coexisted harmoniously with the culture brought by Jamaah Tabligh (JT). This study, utilizing a cultural anthropological approach and cultural resilience theory, along with historical research methods, highlights that the influence of JT's da'wah did not alter the identity of the Temboro people as Nahdliyin members. NU traditions continued to thrive, enriched in worship and social aspects. Several factors supported the persistence of NU traditions, including the kiai's background, Al-Fatah Islamic Boarding School's influence, and community support.